2020
DOI: 10.1111/ajt.15742
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of 18F-FDG PET/CT imaging and urinary CXCL9/creatinine levels in kidney allograft subclinical rejection

Abstract: Subclinical kidney allograft acute rejection (SCR) corresponds to “the unexpected histological evidence of acute rejection in a stable patient.” SCR detection relies on surveillance biopsy. Noninvasive approaches may help avoid biopsy‐associated complications. From November 2015 to January 2018, we prospectively performed positron emission tomography/computed tomography (PET/CT) after injection of F18‐fluorodeoxyglucose (18F‐FDG) in adult kidney transplant recipients with surveillance biopsy at ~3 months postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Compared to serum creatinine, CXCL9 indicates graft rejection earlier and more sensitively [ 3 , 51 , 59 ]. We could show that CXCL9 is highly elevated in urine of KTRs with AMR, which is in line with results of others [ 54 ]. Of note, the CXCL9 mean level was higher in AMR than in TCMR urine samples and CXCL9 was not significantly increased in serum and urine of TCMR patients of the cohorts reported here.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to serum creatinine, CXCL9 indicates graft rejection earlier and more sensitively [ 3 , 51 , 59 ]. We could show that CXCL9 is highly elevated in urine of KTRs with AMR, which is in line with results of others [ 54 ]. Of note, the CXCL9 mean level was higher in AMR than in TCMR urine samples and CXCL9 was not significantly increased in serum and urine of TCMR patients of the cohorts reported here.…”
Section: Discussionsupporting
confidence: 93%
“…CXCL9 has previously been shown to have diagnostic potential as urine biomarker within TCMR [ 52 , 53 , 54 , 55 , 56 , 57 ] and BK virus nephropathy together with CXCL10 [ 58 ]. Compared to serum creatinine, CXCL9 indicates graft rejection earlier and more sensitively [ 3 , 51 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This rapid imaging technique does not cause any side-effect in patients with renal failure from normal to mildly reduced GFR to end-stage renal disease. Furthermore, we have recently showed that 18 F-FDG PET/CT may help rule out subclinical rejection in stable KTR, with a negative predictive value of 98% 23 . Our results support conclusions of previous studies which showed that the uptake of 18 F-FDG by kidneys in non-transplant patients and in KTR is not influenced by renal function 24,25 , and that the alteration of GFR does not significantly compromise the clearance of background activity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism. PET-derived uptake of [18F]fluorodeoxyglucose (FDG) is a powerful index of kidney metabolism, 50 and 2-tert-butyl-4-chloro-5-[6-(4-[( 18) F]fluorobutoxy)pyridin-3-ylmethoxy]-2H-pyridazin-3-one ( 18 F-BCPP-BF) uptake detects mitochondrial function in vivo, 27 but both are limited by radioactivity and low spatial resolution. Hyperpolarized-carbon-13 MRI is an emerging technique based on enzymatic conversion of injected hyperpolarized substrates, which provides both chemical and spatial information.…”
Section: I N I R E V I E Wmentioning
confidence: 99%